Neural Processing Differences of Facial Emotions Between Human and Vehicles: Evidence From an Event-Related Potential Study - Liu, Zhuo; Du, Wenjun; Sun, Zhongrui; Hou, Guanhua; Wang, Zhuonan (Frontiers in Psychology, 2022)
Vehicle “faces” are a crucial factor influencing consumer intention to purchase gasoline and electric vehicles. However, little empirical evidence has demonstrated whether people process a vehicle’s face similarly to a human’s face. We investigated the neural processing relationship among human facial emotions and facial emotions of gasoline and electric vehicles using a 2 (emotional) × 3 (face type) repeated measures design and electroencephalograph (EEG) recordings. The results showed that human faces appear to share a partly similar neural processing mechanism in the latency of 100–300 ms, and that both human and vehicle faces elicited the ERP components N170, EPN, and P2. The large EPN and P2 suggest that gasoline vehicle facial emotions can be perceived more efficiently than those of electric vehicles. These findings provide an insight for vehicle designers to better understand the facial emotions presented by cars.